A method out of madness [professional profile]. - Cass, S. (IEEE spectrum)
This paper presents an interview with David Allen, author of the self-help book entitled "Getting Things Done: The Art of Stress-Free Productivity". In the interview, Allen discusses his ideas on how people can be more organized and become more productive with the aid of various software and high-tech gadgets.